Vigabatrin Monotherapy for Infantile Spasms - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The successful management of 21 children with infantile spasms and hypsarrhythmia using vigabatrin monotherapy is reported from the Alder Hey Children's Hospital, Liverpool, UK.